Research on Tartaric Acid as a Retardant of the Solidification Process of Well-Well Packing Solutions - Orlovskyi, V. M.; Biletskyi, V. S.; Desna, N. A. (VÚRUP, 2025)
This study explores the development of an effective retarding reagent for solidifying (thickening) well-packing solutions used in the cementing process of deep oil and gas wells. This research investigates the handling ability of packing cement with TA additives in environments that simulate reservoir conditions. The main aim is to identify and evaluate an effective retarding agent for solidifying (thickening) well-packing solutions. The retardant for solidifying (thickening) well-packing solutions under consideration should meet the following requirements: a broad operating temperature range, cost-effectiveness, and environmental friendliness.
Дослідження винної кислоти як сповільнювача процесу затвердіння розчинів для пакування свердловин
Keywords: well-packing solution; handling ability; rheological properties; solidification retardants; well-packing; solutions